Factors influencing entrepreneurship success during covid-19 pandemic in Indonesia - Andrie Yuswanto; Usep Suhud; Dedi Purwana; Choirul Anwar (Monas: Jurnal Inovasi Aparatur, 2021)
The Covid-19 pandemic disaster in Indonesia has caused the economy to be the most affected sector. In order to provide solutions for the government in improving the economy through small and medium enterprises, an investigation on business and entrepreneurship solutions is required to support the economy. This study aims to analyze the determinants of entrepreneurial success when a disaster occurs, such as natural disasters, war, and the Covid-19 pandemic as it is today. Business experience, entrepreneurship education, innovation in business, and strategies to produce successful entrepreneurs, are variables that will be tested. The respondents are people who have had experience selling products online. Two hundred seventeen (217) respondents have participated in a questionnaire survey which was created and distributed online through social media. Data validity and data reliability were tested using the Windows SPPS 25.0 application, followed by analyzing data with Structural Equation Model (SEM) using the Windows Amos 23.0 application. The quantitative research results show that strategy affects entrepreneurial success; however, business experience, entrepreneurship education, and business innovation have not related to entrepreneurial success. The research analysis influences the importance of the strategies identified in dealing with a business to be successful. The contribution resulting from this research is how the small and medium enterprises should respond to their efforts in becoming successful entrepreneurs using good business strategies.